A new species of lapwing (Charadriidae: Vanellus) from the late Pliocene of central Australia. (2nd October 2018) - De Pietri, Vanesa L.; Scofield, R. Paul; Prideaux, Gavin J.; Worthy, Trevor H.
ABSTRACT: We describe a new species of lapwing plover from the late Pliocene Kanunka Local Fauna of South Australia (3.6–2.6 mya). Vanellus liffyae sp. nov. is based on an almost complete coracoid, which is most similar in morphology to that of the Masked Lapwing ( Vanellus miles ). Nevertheless, it differs from this species and from the Banded Lapwing ( V. tricolor ), the only other extant resident Australian species, in size and other morphological details. A monophyletic Australasian group including V. tricolor and the two subspecies of V. miles (i.e. miles and novaehollandiae ) had been previously recovered from phenotypic data and is here supported by analyses of COI data. We conclude that, based on the material available for study, Vanellus liffyae sp. nov. is a member of the Australasian clade, which was present in Australia minimally by 3 mya. How Vanellus liffyae sp. nov. relates to the extant taxa within this clade, however, is still unclear. https://rn:lsid:zoobank.org:pub:55AE3295-F3D6-40FC-810C-8277A75696E0